Fever beach [large type] - Hiaasen, Carl (Random House Large Print, 2025)
"The afternoon of September first, dishwater-gray and rainy, a man named Dale Figgo picked up a hitchhiker on Gus Grissom Boulevard in Tangelo Falls, Florida. The hitchhiker, who reminded Figgo of Danny DeVito, asked for a lift to the interstate. Figgo said he'd take him there after finishing an errand. ... Figgo, it turns out, is the only hate-monger ever to be kicked out of the Proud Boys for being too dumb and incompetent. On January 6, 2021 he thought he was defacing a statue of Ulysses S. Grant, but he wound up spreading feces allover a statue of James Zacharia George, a Civil War Confederate warleader. Figgo's already messy life is about to get more complicated, thanks to two formidable adversaries. Viva Morales is a newly transplanted Floridian, a clever woman recently taken to the cleaners byher ex-husband, now working at the Mink Foundation, a supposedly philanthropical organization, and renting a room in Figgo's apartment because there's no place else she can afford. Twilly Spree has an anger management problem, especially when it comes to those who defacethe environment, and way too many inherited millions of dollars. He's living alone a year after his dog died, two years after he sank acity councilman's party barge, and three years after his divorce. Viva and Twilly are plunged into a mystery--involving dark money and darker motives--they are determined to solve, and become entangled in a world populated by some of Hiaasen's most outrageous characters:Claude and Eletra Mink--billionaire philanthropists with way too much plastic surgery and a secret right-wing agenda--and Congressman Clure Boyette--who dreams of being Florida's (and maybe America's) most important politician. The only things standing in his way are hislove for hookers and young girls, and his total lack of intelligence. We meet Noel Kristianson--a Scandinavian agnostic injured when Figgo thinks he's a Jewish threat to humanity and runs him over with his car; Jonus Onus--Figgo's partner in white power idiocy; and many, many more. Hiaasen ties them all together and delivers them to their appropriate fates, in his wildest and most entertaining novel to date."--Provided by publisher.